Prevalence, risk factors, impact and management of constipation among adults in Urumqi, China: a cross-sectional survey - Shi, Lingyun; Shi, Li; Wei, Minghui; Zhang, Mengke; Zhang, Yuan; Li, Jiaxue; Maimaiti, Palida (Frontiers in Nutrition, 2024)
Constipation, a prevalent gastrointestinal disorder, significantly impacts quality of life.This study aimed to investigate the prevalence, risk factors, and implications of constipation in Urumqi City. A cross-sectional survey was conducted from July to August 2023, involving 1,386 participants aged 20 to 80 years. Data were collected via a self-administered questionnaire, with constipation severity assessed using the Patient Assessment of Constipation Symptoms (PAC-SYM) scale. Key findings indicated that various factors, including residing in rural areas, outdoor work, and sleep disorders, were positively correlated with higher PAC-SYM scores. Conversely, higher daily water intake and certain dietary patterns showed negative correlations.Additionally, increased constipation severity was associated with greater physiological strain and psychosocial concerns (all P<0.05), emphasizing the disorder's profound effect on quality of life. These findings underscore the need for comprehensive management strategies in Urumqi, considering its diverse lifestyle and dietary factors.